2022
DOI: 10.3390/jof8010055
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted and Targeted LC-MS/MS Based Metabolomics Study on In Vitro Culture of Phaeoacremonium Species

Abstract: Grapevine (Vitis vinifera L.) can be affected by many different biotic agents, including tracheomycotic fungi such as Phaeomoniella chlamydospora and Phaeoacremonium minimum, which are the main causal agent of Esca and Petri diseases. Both fungi produce phytotoxic naphthalenone polyketides, namely scytalone and isosclerone, that are related to symptom development. The main objective of this study was to investigate the secondary metabolites produced by three Phaeoacremonium species and to assess their phytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
5
0
2
Order By: Relevance
“…More recently, the first study of both untargeted and targeted LC-MS/MS-based metabolomics to investigate differences in the metabolic composition of organic extracts of three Phaeoacremonium species involved in Esca was reported [ 140 ]. Several isolates of P. italicum , P. alvesii , and P. rubrigenum were grown in vitro, and the culture filtrates, and organic extracts, were assayed for phytotoxicity.…”
Section: Metabolomics Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the first study of both untargeted and targeted LC-MS/MS-based metabolomics to investigate differences in the metabolic composition of organic extracts of three Phaeoacremonium species involved in Esca was reported [ 140 ]. Several isolates of P. italicum , P. alvesii , and P. rubrigenum were grown in vitro, and the culture filtrates, and organic extracts, were assayed for phytotoxicity.…”
Section: Metabolomics Studiesmentioning
confidence: 99%
“…The absolute quantification revealed that the amount of ( 1 ) and ( 2 ) differed within and among fungal species. Finally, further analysis is needed to identify the unknown metabolites detected in the untargeted analysis [ 140 ].…”
Section: Metabolomics Studiesmentioning
confidence: 99%
“…La enfermedad de Petri o también llamada como "black goo", "young grapevine decline" o "young yesca", es muy importante en muchos países productores de vid (Gramaje et al, 2018;Battiston et al, 2021). Actualmente, se han reportado 63 especies de Phaeoacremonium, de las cuales 37 se han aislado de vid (Reveglia et al, 2022;Spies et al, 2018). Las diferentes especies de Phaeoacremonium spp., Phaeomoniella chlamydospora y Cadophora luteo-olivacea se han asociado con la enfermedad de Petri en vides jóvenes (<5 años) y con la enfermedad de yesca en vides adultas (>5 años).…”
Section: Introductionunclassified
“…These health benefits of dark teas can be attributed to its diverse phytochemical composition [ 5 ]. Liquid chromatography-mass spectrometry (LC-MS) based untargeted metabolomics is extensively used to detect unknown metabolite components in food products [ 6 7 8 ]. To identify known metabolites, the common approach is to match a library of standard spectra based on the exact mass of the precursor ion and tandem mass spectra (MS 2 spectra of cleaved fragments).…”
Section: Introductionmentioning
confidence: 99%